2015
DOI: 10.3109/02699052.2015.1088963
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacological intervention of the p75NTR pathway alters morphological and behavioural recovery following traumatic brain injury in mice

Abstract: Many of the pathological and behavioural consequences of TBI might be due to activation of the pro-neurotrophin/p75 toxic pathway overriding the protective mechanisms of the mature neurotrophin/Trk pathway. Targeting p75 can be a novel strategy to counteract the damaging effects of TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 110 publications
8
53
0
Order By: Relevance
“…6A). We and others have observed this behavior in previous stud- ies (Cernak et al, 2014;Chen et al, 2014;Rowe et al, 2014;Alder et al, 2016), and since it was independent of the injury, we did not investigate this matter further.…”
Section: Tg-c73a Mice Perform Better Than Non-tg and Tg-wt Mice On Thmentioning
confidence: 76%
See 2 more Smart Citations
“…6A). We and others have observed this behavior in previous stud- ies (Cernak et al, 2014;Chen et al, 2014;Rowe et al, 2014;Alder et al, 2016), and since it was independent of the injury, we did not investigate this matter further.…”
Section: Tg-c73a Mice Perform Better Than Non-tg and Tg-wt Mice On Thmentioning
confidence: 76%
“…The findings reported here that show that oxidation of K ϩ channels contribute to cognitive impairment underscore the high degree of conservation of this mechanism of neuronal vulnerability and further broaden its potential relevance. For example, it is well established that the aging hippocampus of rodents develops hyperexcitability (Landfield et al, 1986;Barnes et al, 1987;Barnes, 1994;Papatheodoropoulos and Kostopoulos, 1996), and it may not be coincidental that KCNB1 undergoes oxidation in the brains of naturally aging mice (Cotella et al, 2012). Moreover, KCNB1 channels are oxidized in hippocampal neurons of the 3x-Tg-AD mouse where they promote hyperexcitability (Frazzini et al, 2016), while inhibition of Src kinases attenuates microgliosis in BV2 murine cells incubated with ␤-amyloid oligomers (Dhawan and Combs, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous investigation, the assessment of synaptic proteins utilized the penumbra as opposed to the cortex directly below the injury location. There are several instances where a natural compound has been shown to significantly reduce secondary injury cascades but fail to improve cognitive performance in the MWM [1, 11, 21]. Somewhat surprising is the fact that caffeic acid, which is one of the main components of PYC, has been shown to significantly reduce lesion volume and improve cognition when administered post-trauma [56].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with animal TBI models suggested that some of the pathological and behavioral effects of TBI might be due to damage signaling activated by pro-neurotrophin/p75 association, which prevails over the protective signaling activated by mature neurotrophin/Trk binding [118]. Trk-signals are normally required for neuronal maintenance and function, and defects in Trk activation are associated with early stages of neurodegeneration [119,120,121].…”
Section: What Are the Roles Of Neurotrophins After Acute Neural Inmentioning
confidence: 99%